2022
DOI: 10.1002/prca.202200003
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and lipidomic biomarkers in the diagnosis and progression of inflammatory bowel disease – a review

Abstract: Purpose There is an increasing prevalence of inflammatory bowel disease (IBD) and to date, no effective treatment has been developed and the exact etiology of this disease remains unknown. Nevertheless, a growing number of proteomic and lipidomic studies have identified certain proteins and lipids which can be used successfully in patients to improve diagnoses and monitoring of treatment. Experimental Design We have focused on the applications of proteins and lipids for IBD diagnostics, including differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…These studies have identified a large variety of lipids associated with CD. However, only a few studies have overlapped in the analysis of specific lipids [ 137 ]. There is also no consensus on the best specimen for analysis in the current literature—blood, tissue or faeces—which have varying levels of invasiveness and ease of collection [ 138 ].…”
Section: Lipidomicsmentioning
confidence: 99%
“…These studies have identified a large variety of lipids associated with CD. However, only a few studies have overlapped in the analysis of specific lipids [ 137 ]. There is also no consensus on the best specimen for analysis in the current literature—blood, tissue or faeces—which have varying levels of invasiveness and ease of collection [ 138 ].…”
Section: Lipidomicsmentioning
confidence: 99%